2016
DOI: 10.1080/10408444.2016.1214680
|View full text |Cite|
|
Sign up to set email alerts
|

Genotoxicity Expert Panel review: weight of evidence evaluation of the genotoxicity of glyphosate, glyphosate-based formulations, and aminomethylphosphonic acid

Abstract: published a monograph concluding there was strong evidence for genotoxicity of glyphosate and glyphosate formulations and moderate evidence for genotoxicity of the metabolite aminomethylphosphonic acid (AMPA). These conclusions contradicted earlier extensive reviews supporting the lack of genotoxicity of glyphosate and glyphosate formulations. The IARC Monograph concluded there was strong evidence of induction of oxidative stress by glyphosate, glyphosate formulations, and AMPA. The Expert Panel reviewed the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 82 publications
3
37
0
Order By: Relevance
“…The genetic toxicology Expert Panel (Brusick et al 2016) considered published studies reviewed in the IARC monograph and additional published studies identified by literature searches or from review articles, not considered by IARC. These included both genetic toxicology studies and studies of oxidative stress.…”
Section: Genetic Toxicity and Oxidative Stress Datamentioning
confidence: 99%
“…The genetic toxicology Expert Panel (Brusick et al 2016) considered published studies reviewed in the IARC monograph and additional published studies identified by literature searches or from review articles, not considered by IARC. These included both genetic toxicology studies and studies of oxidative stress.…”
Section: Genetic Toxicity and Oxidative Stress Datamentioning
confidence: 99%
“…A large team of researchers including 96 research professors from 22 countries worldwide (Portier et al, 2016) analyzed the data. Taking a contrary position were a set of six studies published in the journal Critical Reviews in Toxicology (Acquavella et al, 2016;Brusick et al, 2016;McClellan, 2016;Solomon, 2016;Williams et al, 2016a,b), sponsored by Monsanto and other members of the pesticide industry, as declared in the papers themselves. These reviews focused on the carcinogenicity, genotoxicity of glyphosate and exposures to it, but considered partly the same data and followed the same concept published in a previous risk assessment by the same lead author (Williams et al, 2000).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…The health issue was reignited in 2015 when the International Agency for Research on Cancer (IARC) published a monograph concluding that glyphosate is ‘probably carcinogenic to humans’ . The US Environmental Protection Agency and others have since concluded that glyphosate is likely not a carcinogen, but the firestorm over its safety continues in both popular press and scientific publications . In addition, concerns are often raised about the safety of glyphosate formulations that contain the original tallow amine ethoxylate ‘Roundup surfactant.’ This surfactant type has known aquatic and eye toxicity issues that are commonly addressed with mandatory application restrictions and requirements for operators to wear personal protective equipment (PPE).…”
Section: Future For Glyphosate and Glyphosate Cropsmentioning
confidence: 99%